Conciliation strategies in the New Procedure Code: A look through game theory - Cordeiro, Thiago Ferreira (2023)
The New Code of Civil Procedure affirmed the principle of cooperation in several devices, especially in its art. 6th. One of the most notorious expressions of that principle is the mandatory designation of a conciliation hearing for the self-composition of the parties, pursuant to art. 334 of encoding. The concern of the new law to make procedural rules more flexible, streamline procedures and resolve cases through conciliation is based on the need to modernize the exercise of jurisdiction in the face of the current demands of society. In this way, several institutes were created by the legislator, while others are suggested by the doctrine, with the aim of fostering the conciliatory interest of the parties. However, the success of the measures, in some contexts, has still been unsatisfactory. Based on game theory, it is possible to equate the variables involved in the decision-making process of those under jurisdiction regarding conciliation, thus allowing a critical analysis of the institutes used and the suggestion of what could be changed to optimize the implementation of the legislator's political choice.